Pelvic Intraoperative Neuromonitoring Prevents Dysfunction in Patients With Rectal Cancer: Results From a Multicenter, Randomized, Controlled Clinical Trial of a NEUROmonitoring System (NEUROS). Issue 4 (30th April 2023) - Kneist, Werner; Ghadimi, Michael; Runkel, Norbert; Moesta, Thomas; Coerper, Stephan; Benecke, Claudia; Kauff, Daniel W.; Gretschel, Stephan; Gockel, Ines; Jansen-Winkeln, Boris; Lang, Hauke; Gorbulev, Stanislav; et al.
Abstract : Objective: This NEUROmonitoring System (NEUROS) trial assessed whether pelvic intraoperative neuromonitoring (pIONM) could improve urogenital and ano-(neo-)rectal functional outcomes in patients who underwent total mesorectal excisions (TMEs) for rectal cancer. Background: High-level evidence from clinical trials is required to clarify the benefits of pIONM. Methods: NEUROS was a 2-arm, randomized, controlled, multicenter clinical trial that included 189 patients with rectal cancer who underwent TMEs at 8 centers, from February 2013 to January 2017. TMEs were performed with pIONM (n=90) or without it (control, n=99). The groups were stratified according to neoadjuvant chemoradiotherapy and sex, with blocks of variable length. Data were analyzed according to a modified intention-to-treat protocol. The primary endpoint was a urinary function at 12 months after surgery, assessed with the International Prostate Symptom Score, a patient-reported outcome measure. Deterioration was defined as an increase of at least 5 points from the preoperative score. Secondary endpoints were sexual and anorectal functional outcomes, safety, and TME quality. Results: The intention-to-treat analysis included 171 patients. Marked urinary deterioration occurred in 22/171 (13%) patients, with significantly different incidence between groups (pIONM: n=6/82, 8%; control: n=16/89, 19%; 95% confidence interval, 12.4–94.4; P =0.0382). pIONM was associated with better sexual and ano-(neo)rectal function. At least 1 serious adverse event occurred in 36/88 (41%) in the pIONM group and 53/99 (54%) in the control group, none associated with the study treatment. The groups had similar TME quality, surgery times, intraoperative complication incidence, and postoperative mortality. Conclusion: pIONM is safe and has the potential to improve functional outcomes in rectal cancer patients undergoing TME.